2021
DOI: 10.1007/s11356-021-14420-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fine recycled aggregate on the strength and durability properties of concrete modified through two-stage mixing approach

Abstract: To overcome the scarcity of river sand and dumping of construction and demolition wastes, the fine recycled aggregate (FRA) collected from C&D wastes is being utilized as a replacement to river sand. Many earlier studies reported that the higher water absorption of fine recycled aggregate and weak interfacial transition zone (ITZ) resulted in the development of the concrete with less strength and durability requirements. This study surmounts the above two factors through pre-saturation and a two-stage mixing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Regarding the percentage of substitution by stone dust, the permeability for chloride ions increases with the increase in the SD percentage. In general, it can be seen that with 0% of SD, electric flux is around 1260 C [40,86,127,130]; with 25% of SD substitution this value rises to 1713 C [40,130], with 50% it rises to 2033 C [127,130], and with 100%, it is 4000 C [130]. According to ASTM C1202 [129], electric flux in the range of 2000-4000 C is classified as moderate ion permeability.…”
Section: Durabilitymentioning
confidence: 99%
“…Regarding the percentage of substitution by stone dust, the permeability for chloride ions increases with the increase in the SD percentage. In general, it can be seen that with 0% of SD, electric flux is around 1260 C [40,86,127,130]; with 25% of SD substitution this value rises to 1713 C [40,130], with 50% it rises to 2033 C [127,130], and with 100%, it is 4000 C [130]. According to ASTM C1202 [129], electric flux in the range of 2000-4000 C is classified as moderate ion permeability.…”
Section: Durabilitymentioning
confidence: 99%
“…RFA is one of the important reasons for the performance of concrete due to its excessive water absorption; however, the use of moisture in the two-part addition, i.e., the two-stage mixing method (TSMA), can effectively prevent the excessive water absorption of RFA [ 68 ]. The performance of concrete with different RFA replacement rates prepared by the normal mixing method and TSMA was investigated, and it was found that the drying shrinkage values of all RFAc using TSMA were lower than those of the concrete prepared by the normal mixing method, mainly because of the higher compactness and better ITZ of RFAc prepared by TSMA [ 69 ].…”
Section: Drying Shrinkagementioning
confidence: 99%
“…The compressive behavior of the cylinder under uniaxial compressive tests was studied. As is well known, the stress-strain relationship of the structural member was essential for compressive behavior [27][28][29][30]. For instance, Chang et al [31] investigated the effect of the recycled aggregate (RA) replacement ratio on the stressstrain behavior of different concrete strengths.…”
Section: Introductionmentioning
confidence: 99%